2020
DOI: 10.1186/s40814-020-00617-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of summer programming on the obesogenic behaviors of children: behavioral outcomes from a quasi-experimental pilot trial

Abstract: Background: Children from low-income families experience accelerated BMI gain and learning loss during summer. Healthy Summer Learners (HSL) addresses accelerated BMI gain and academic learning loss during summer by providing academic-and health-focused programming. This manuscript reports the effects of HSL on underlying obesogenic behaviors (i.e., physical activity, screen time, sleep, diet) that lead to accelerated summer BMI gain, a necessary first step to informing a future randomized controlled trial of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Finally, when exclusively nonschool days were explored (i.e., nonschool weekdays or weekend days), rural children in this study attending a day camp, program, or sports practice on a nonschool day were more active (+23 minutes MVPA), less sedentary (-55 minutes/day), and engaged in less screen time (-75 minutes/day) compared with days they did not attend. This finding lends support to the growing body of evidence showing other ''school-like'' environments-such as day camps and programs 19,20,22,53 can have a positive impact on obesogenic behaviors of all children. These findings highlight a potential mechanism through which future interventions can be centered on; implementing structured programming on days or times of the year when rural children may be removed from consistent school-like environments.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, when exclusively nonschool days were explored (i.e., nonschool weekdays or weekend days), rural children in this study attending a day camp, program, or sports practice on a nonschool day were more active (+23 minutes MVPA), less sedentary (-55 minutes/day), and engaged in less screen time (-75 minutes/day) compared with days they did not attend. This finding lends support to the growing body of evidence showing other ''school-like'' environments-such as day camps and programs 19,20,22,53 can have a positive impact on obesogenic behaviors of all children. These findings highlight a potential mechanism through which future interventions can be centered on; implementing structured programming on days or times of the year when rural children may be removed from consistent school-like environments.…”
Section: Discussionsupporting
confidence: 75%
“…Exploring behaviors on different days is of paramount importance given the evidence that obesogenic behaviors are more favorable (e.g., increased physical activity and reduced sedentary time/ screen time) in urban-dwelling children during school days or when children are in a ''school-like'' environment (e.g., day camp/program) compared with days they are not. [17][18][19][20][21][22] There is a need for additional studies of rural children's obesogenic behaviors, specifically research exploring behaviors across different days to inform future intervention strategies targeting rural children and families. The purpose of this study was to provide preliminary evidence of rural children's physical activity, sedentary time, sleep, diet and screen time during school days, nonschool weekdays, and weekend days.…”
mentioning
confidence: 99%
“…The findings of the current study align with past studies that have found children are less active and engage in more screen‐time during periods of less structure (i.e., summer, weekends, or holidays). 20 , 28 , 33 , 42 , 43 , 44 , 45 Given that children who are Black and children from low‐income households experience more dramatic accelerations in BMI during the summer than their White and middle‐to‐high‐income counterparts, 31 the finding in this study that the summer negatively impacted the MVPA of children who are Black and eligible for FRPL to a greater degree than children who are White or not eligible for FRPL is important. This finding suggests a specific behavioral mechanism, decreased MVPA, that may partially explain the greater increases in BMI gain during the summer for children who are Black and eligible for FRPL.…”
Section: Discussionmentioning
confidence: 79%
“…The findings of the current study align with past studies that have found children are less active and engage in more screen-time during periods of less structure (i.e., summer, weekends, or holidays). 20,28,33,[42][43][44][45] Given that children who are Black and children from low-income households experience more dramatic accelerations in BMI during the summer than their White and middle-to-highincome counterparts, 31 days and during the summer when compared to the school year. 21,33,48,49 However, these same studies show that children's bedtimes and wake times shift later and become more variable during the summer.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Since its publication in 2017, the SDH has informed several studies that have purposefully compared obesogenic behaviors during structured versus less-structured times, such as summer versus school months [9,10], summer camp/program days versus non camp/program days [11][12][13], and school-days versus non-school days [14][15][16]. Together, these studies align with the notion that children's obesogenic behaviors are more favorable on structured versus less-structured days, yet are limited by small sample sizes and specific population demographics, making it challenging to generalize findings.…”
Section: Introductionmentioning
confidence: 99%